Penerapan media pembelajaran papan keranjang pembelajaran IPAS kelas IV SD - Septia adelia putri; efryda savita anjarwati; Isna Rahmawati . (CV. ITTC INDONESIA, 2024)
This research aims to determine the application of basket board learning media for science and science learning in class IV elementary schools. This type of research uses a qualitative descriptive method. The instrument used is documentation. The subjects of this research were 19 grade IV students at SD Negeri 1 Towangsan for the 2023/2024 academic year. The results of this research are that by using basket board media students understand the material provided better, create a pleasant learning atmosphere and make students more active in learning.